2014
DOI: 10.1016/j.febslet.2014.12.022
|View full text |Cite
|
Sign up to set email alerts
|

Effects of detyrosinated tubulin on Na+,K+‐ATPase activity and erythrocyte function in hypertensive subjects

Abstract: Edited by Judit OvádiThis paper is dedicated in memory of Marina Rafaela Amaiden (''Rafa'') who will remain forever in our hearts. in a 50% reduction in NKA activity. We demonstrate here that detyrosinated tubulin, which is increased in hypertensive erythrocytes membranes, enhances the inhibitory effect of acetylated tubulin on NKA activity. Moreover, we report a reduced content and activity of the enzyme tubulin tyrosine ligase in erythrocytes of hypertensive subjects. Such alterations are related to changes … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
20
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 16 publications
(20 citation statements)
references
References 38 publications
0
20
0
Order By: Relevance
“…Touyz and Milne stated that Na + /K + -ATPase, Mg 2+ -ATPase, and Ca 2+ -ATPase activities of erythrocyte membrane were downregulated in hypertensive patients [53]. And further studies found that the inhibited ATPase activities suppress the cation transports, inducing hypertension [24]. In our experiment, we deduced that AlCl 3 disturbs the function of erythrocyte membrane by decreasing the activities of Na + /K + -ATPase, Mg 2+ -ATPase, and Ca 2+ -ATPase, and consequently, induces hypertension.…”
Section: Discussionmentioning
confidence: 98%
See 1 more Smart Citation
“…Touyz and Milne stated that Na + /K + -ATPase, Mg 2+ -ATPase, and Ca 2+ -ATPase activities of erythrocyte membrane were downregulated in hypertensive patients [53]. And further studies found that the inhibited ATPase activities suppress the cation transports, inducing hypertension [24]. In our experiment, we deduced that AlCl 3 disturbs the function of erythrocyte membrane by decreasing the activities of Na + /K + -ATPase, Mg 2+ -ATPase, and Ca 2+ -ATPase, and consequently, induces hypertension.…”
Section: Discussionmentioning
confidence: 98%
“…The abnormalities in sodium transport of erythrocyte membrane were found in patients with essential hypertension [21,22]. Further research showed that the activity of membrane-bound (Na + /K + )-ATPase was downregulated in hypertensive patients [23], and the inhibition of ATPase activity disturbed ion transport of membrane, thus, leading to an increase in blood pressure [24]. Kaczmarska et al proved that disturbed membrane protein and impaired oxygen release of erythrocyte membrane contributed to the development of hypertension [25].…”
Section: Introductionmentioning
confidence: 99%
“…In hypertension, this mechanism is important because the decrease in the content and the enzymatic activity of TTL in hypertensive erythrocytes (Amaiden et al, 2015) increases the level of detyrosinated tubulin, which has an inhibitory effect on NKA activity, according to the mentioned results. This would explain why the cells of hypertensive individuals accumulate Na + .…”
Section: Perspectivesmentioning
confidence: 90%
“…In addition, the regulation of Na + /K + homeostasis, also dependent on the tubulin–NKA interaction, opens new perspectives in different pathologies in which the homeostasis of these ions is unbalanced. In hypertension, this mechanism is important because the decrease in the content and the enzymatic activity of TTL in hypertensive erythrocytes (Amaiden et al, ) increases the level of detyrosinated tubulin, which has an inhibitory effect on NKA activity, according to the mentioned results. This would explain why the cells of hypertensive individuals accumulate Na + .…”
Section: Perspectivesmentioning
confidence: 96%
“…In hypertensive patients the level of detyrosinated tubulin was higher in the sedimentable fraction. Consequent translocation of detyrosinated tubulin to the plasma membrane enhanced the inhibitory effect of tubulin on Na,K-ATPase activity resulting in reduced RBC deformability (Amaiden et al 2015).…”
Section: Hypertensionmentioning
confidence: 99%